2023
DOI: 10.3390/toxics11121027
|View full text |Cite
|
Sign up to set email alerts
|

Structural Malformations in the Neonatal Rat Brain Accompany Developmental Exposure to Ammonium Perchlorate

Mary E. Gilbert,
Katherine L. O’Shaughnessy,
Kiersten S. Bell
et al.

Abstract: Environmental contaminants are often flagged as thyroid system disruptors due to their actions to reduce serum thyroxine (T4) in rodent models. The presence of a periventricular heterotopia (PVH), a brain malformation resulting from T4 insufficiency, has been described in response to T4 decrements induced by pharmaceuticals that reduce the hormone synthesis enzyme thyroperoxidase. In this report, we extend these observations to the environmental contaminant perchlorate, an agent that interferes with thyroid st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Based on this study alone, it cannot be concluded that fetal brain TH measurements do not provide added value to serum TH measurements in the CTA with small group size. Recent research studies using environmental contaminants on TH disruption were conducted using varying numbers of animals, e.g., less than or about 10 animals per dose ( Ramhøj et al, 2018 , Ramhøj et al, 2022 , Gilbert et al, 2021 , Gilbert et al, 2022 , Gilbert et al, 2023 ), 15–16 animals per dose ( Ramhøj et al, 2020 ), or two balanced blocks and comprised three treatment groups of 22 dams each ( Ramhøj et al, 2022 ). Although these are informative, they are not sufficient to draw conclusions because brain TH concentrations were not measured in all cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on this study alone, it cannot be concluded that fetal brain TH measurements do not provide added value to serum TH measurements in the CTA with small group size. Recent research studies using environmental contaminants on TH disruption were conducted using varying numbers of animals, e.g., less than or about 10 animals per dose ( Ramhøj et al, 2018 , Ramhøj et al, 2022 , Gilbert et al, 2021 , Gilbert et al, 2022 , Gilbert et al, 2023 ), 15–16 animals per dose ( Ramhøj et al, 2020 ), or two balanced blocks and comprised three treatment groups of 22 dams each ( Ramhøj et al, 2022 ). Although these are informative, they are not sufficient to draw conclusions because brain TH concentrations were not measured in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…Results from the present study revealed reduced brain T4 concentrations in GD20 fetuses of approximately 30 % for the 1000 and 1500 ppm exposures with NaPB. As the persistence of TH reduction after birth, in addition to the extent of TH decrease during the fetal period, is considered a significant factor in heterotopia formation ( O’Shaughnessy et al, 2018 , O'Shaughnessy et al, 2019 Gilbert et al, 2023 ), the assessment of offspring brain TH concentrations and heterotopia formation in the postnatal test cohort of the CTA with NaPB becomes important. We will discuss this issue in a separate paper on the postnatal test cohort with NaPB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation